Agricultural waste-derived superabsorbent hydrogels: Preparation, performance, and socioeconomic impacts. (1st April 2020) - Li, Simeng; Chen, Gang
Abstract: Most agricultural wastes are rich in cellulose. Through chemical and/or mechanical processes, nanocellulose can be extracted to produce superabsorbent hydrogels. As soil amendments, superabsorbent hydrogels act as water and nutrient reservoirs when applied in agricultural fields. This article reviews the recent advances in agricultural waste-derived nanocellulose-based superabsorbent hydrogels and discusses the possible impacts of their applications in agriculture. The strengths and weaknesses of different current processes and techniques for nanocellulose extraction and hydrogel synthesis are compared. It is found that chemical methods are generally more cost-effective but may pose a threat to ecosystems, whereas physical methods are environmentally friendly but more complicated and expensive. The economic viability of using these novel superabsorbent hydrogels as soil amendments is also discussed, considering their potentials to reduce irrigation, enhance nutrient retention, and improve crop production. The results in this article indicates that the development of agricultural waste-derived superabsorbent hydrogels promotes environmental sustainability and circular economy in agriculture. The life cycles of new hydrogel products need to be explored in detail before optimal cellulose sources, reagents, and methods can be proposed for improvements. Graphical abstract: Image 10265 Highlights: Nanocellulose can be extracted from agricultural wastes to synthesize hydrogels. Chemical pretreatment and physical treatment optimize nanocellulose extraction. Nanocellulose hydrogels reduce water/fertilizer inputs and increase crop yields. Positive net farm income can be improved by agricultural waste-derived hydrogels. Analyzing environmental impacts and human health risks is urgent for new hydrogels.